Validation of a clinician-administered diagnostic measure of ICD-11 PTSD and complex PTSD: the International Trauma Interview in a clinical sample of military veterans - Ole Melkevik; Anni B. S. Nielsen; Katrine Friis; Caroline Lund; Bjarke W. Schmidt; Sofie Folke (European Journal of Psychotraumatology)
Background: The International Trauma Interview (ITI) is the first clinician-administered diagnostic tool developed to assess posttraumatic stress disorder (PTSD) and Complex PTSD (CPTSD), both recently recognized in the ICD-11. The current study aims to test the construct and discriminant validity of the ITI in a population of treatment-seeking veterans.Method: 124 Danish veterans seeking psychological treatment were interviewed by a group of trained clinicians for ICD-11 PTSD and CPTSD before beginning treatment at the Military Psychological Department in the Danish Defense. A series of confirmatory factor models were estimated in order to identify the extent to which latent variable operationalizations provide potential explanations for the associations between symptoms.Results: Results indicate that symptoms of CPTSD, as measured by the ITI, are best represented by a single higher-order factor. We also found that a bifactor model provided adequate fit to the data. The commonly identified two-factor higher-order model was rejected due to the lack of discriminant validity between PTSD and DSO. The higher order model was found to explain associations between symptoms of CPTSD and symptoms of depression, stress, anxiety, and well-being.Conclusion: The ITI does not fit a two-factor higher-order model in a sample of treatment-seeking Danish veterans. Rather, a single higher order factor shows excellent fit, and is found to explain associations between ITI symptoms and other internalizing symptoms.